Experience of vascular injuries at a military hospital in Korea - Doohun Kim; Soyun Nam; Yoon Hyun Lee; Hojun Lee; Hyun Chul Kim (Journal of Trauma and Injury)
Purpose Vascular injuries require immediate surgical treatment with standard vascular techniques. We aimed to identify pitfalls in vascular surgery for trauma team optimization and to suggest recommendations for trauma and vascular surgeons. Methods We reviewed 28 victims and analyzed the patterns of injuries, methods of repair, and outcomes. Results Ten patients had torso injuries, among whom three thoracic aorta injuries were repaired with thoracic endovascular aortic repair, one left hepatic artery pseudoaneurysm with embolization, and two inferior vena cava with venorrhaphy, three iliac arteries with patch angioplasty or embolization, and three common femoral arteries with bypass surgery or arterioplasty. Four patients had upper extremity injuries, among whom one brachial artery and vein was repaired with bypass surgery after temporary intravascular shunt perfusion, two radial arteries were repaired with anastomoses, and one ulnar artery was repaired with ligation. One radial artery under tension was occluded. Fourteen patients had lower extremity injuries, among whom one superficial femoral artery and vein was repaired with bypass and concomitant ligation of the deep femoral artery and vein, three superficial femoral arteries were repaired with bypass (two concomitant femoral veins with bypass or anastomosis), one deep femoral artery with embolization, two popliteal arteries with bypass or anastomosis, four infrapopliteal transected arteries, one arteriovenous fistula with ligation, and one pseudoaneurysm with bypass. However, one superficial femoral artery and all femoral veins were occluded. One leg replantation failed. Conclusions There are potential complications of vascular access during resuscitative endovascular balloon occlusion of the aorta procedures. Vascular repair should be performed without tension or spasm. Preservation of the harvested vein in papaverine solution and blood while using a temporary intravascular shunt is a method of eliminating spasms.